INTEGRATING SHARIA BUSINESS CONTRACTS: Enhancing Inheritance Management Among the Simalungun Batak Tribe’s Muslim Community - Muhammad Zuhirsyan; Pagar Pagar; Ansari Ansari; Nurhadi Nurhadi (IAIN Ponorogo, 2023)
This research was conducted to find sharia contracts that could be empowered in utilizing inherited assets in the Simalungun Batak Muslim community. This research was field research. The data collection techniques were through interviews and observations and utilizing literature using classical and contemporary fiqh books. The research method was a historical qualitative approach, while the analysis technique used a qualitative descriptive method. The results of the study show that various models of sharia contracts in the utilization of inherited assets can be carried out by the community, such as profit sharing (mudharabah), cooperation (musyarakah), leasing (ijarah), entrusted (wadiah) and waqf. These various sharia contracts can be carried out both between heirs and heirs with other parties. In order to strengthen the implementation of this sharia contract, it is necessary to implement a written contract to strengthen the contract realization process and assist the interests of all parties and for their benefit. The application of this contract can be implemented based on various principles: economic, maqashid, contract, and customary inheritance law principles.